Analisis Faktor-Faktor yang Memengaruhi Pendapatan dan Remitansi Pekerja Migran Non Permanen di Desa Dalundg - Ni Luh Made Ayu Meisya Harsaweni; Luh Gede Meydianawathi (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Population migration is a common phenomenon across Indonesia, particularly migration for employment purposes. One of the major destination areas is Badung Regency, especially Dalung Village in North Kuta District, which serves as a buffer zone for Denpasar City. Its strategic location has attracted a large number of non-permanent migrants. This study aims to analyze the effects of employment status, education, number of family dependents, and working hours allocation on income and remittances, as well as to examine the mediating role of income. A quantitative approach was employed using a sample of 148 respondents selected through probability sampling with a proportionate stratified random sampling technique. Data were analyzed using descriptive statistics and path analysis. The results indicate that employment status has a positive and significant effect on income, while education, number of family dependents, and working hours allocation do not significantly affect income. Regarding remittances, education and income have significant direct effects, whereas employment status, number of family dependents, and working hours allocation do not show significant effects. Furthermore, education indirectly affects remittances through income. In contrast, employment status, number of family dependents, and working hours allocation have no indirect effect on remittances through income. These findings highlight the importance of education and income in influencing remittance behavior among migrant workers.